Social Class, Language, and Academic Achievement: Understanding English Performance in the Context of Bangladesh’s Stratification - Sharmin Rahman Bipasha; MD Nahidul Islam (English Department - University of Sultan Ageng Tirtayasa, 2025)
This study investigates the complex interplay between social class, language, and academic achievement, with a particular focus on English performance among secondary and higher secondary-level students in Bangladesh. A mixed-methods methodology enabled the researchers to acquire quantitative and qualitative responses through stratified sampling from 250 students and 25 teaching staff throughout three districts serving government and non-government educational institutions across rural and urban areas. The quantitative section utilizes ANOVA statistical procedures to determine the relationship between students' economic status together with their command of the language and their results in English academic subjects. Semi-structured teacher interviews, together with classroom observations, provide researchers with qualitative knowledge that explains educational barriers' direct impact on teachers' and students' experiences. The study demonstrates that upper-class students achieve better English results than lower-class students each year. Educational success among students depends on three fundamental factors, which consist of household language practice, educational resource availability, and established teacher expectations. This research shows that English proficiency serves as both an entry point and a source of difficulty in educational progress because it holds essential importance within the educational stratification system. This work enriches research about developing nations' educational inequalities by providing recommendations for policies that combat the linguistic factors responsible for social achievement disparities. The research analysis supports extensive educational changes that must follow Bangladesh's systematic social inequalities and the essential role language plays in determining academic results.